2021
DOI: 10.1111/all.15111
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory roles of three miRNAs on allergen mRNA expression in Tyrophagus putrescentiae

Abstract: Background: Tyrophagus putresecentiae is an important mite species in rural and urban environments, causing sensitization and allergic disease. While evidence suggests that microRNAs (miRNAs) may regulate the expression of allergen-encoding genes, no study has directly investigated this possibility. Here, this gap was addressed by profiling miRNAs and elucidating their target allergen messenger RNAs (mRNAs) in this mite species.Methods: Small RNA and transcriptome libraries were constructed for eggs, larvae, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…224 The immune characteristics of VZV-infected arteries and the specific immune mechanisms involved in VZV-associated neuroinflammation are not fully elucidated. 225,226 While antiviral drugs and corticosteroids are used to treat VZV-associated neuroinflammation, the effectiveness of these treatments is limited, and there is a need for more targeted and effective therapies. 224 While it is known that VZV can have serious clinical consequences in immunocompromised subjects and adults, the specific immune mechanisms that contribute to the pathogenesis of VZV-associated neuroinflammation in these populations are not well understood.…”
Section: Emerging Research Directions and Gaps In Our Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…224 The immune characteristics of VZV-infected arteries and the specific immune mechanisms involved in VZV-associated neuroinflammation are not fully elucidated. 225,226 While antiviral drugs and corticosteroids are used to treat VZV-associated neuroinflammation, the effectiveness of these treatments is limited, and there is a need for more targeted and effective therapies. 224 While it is known that VZV can have serious clinical consequences in immunocompromised subjects and adults, the specific immune mechanisms that contribute to the pathogenesis of VZV-associated neuroinflammation in these populations are not well understood.…”
Section: Emerging Research Directions and Gaps In Our Understandingmentioning
confidence: 99%
“…PHN is the most common and consequential consequence of VZV reactivation, although its aetiology is unclear and its therapy is often ineffectual 224 . The immune characteristics of VZV‐infected arteries and the specific immune mechanisms involved in VZV‐associated neuroinflammation are not fully elucidated 225,226 . While antiviral drugs and corticosteroids are used to treat VZV‐associated neuroinflammation, the effectiveness of these treatments is limited, and there is a need for more targeted and effective therapies 224 .…”
Section: Therapeutic Approaches and Future Directionsmentioning
confidence: 99%
“…To the Editor, Tyrophagus putrescentiae is a medically important mite species causing allergies worldwide. 1,2 More than 20 IgE-reactive components are detectable in T. putrescentiae extracts. 3 The World Health Organization/International Union of Immunological Societies (WHO/IUIS) Allergen Nomenclature Sub-Committee lists 12 allergens from T. putrescentiae: Tyr p 1-3, 7, 8, 10, 13, 20, 28, and 34-36.…”
Section: Chromosome-level Genomic Assembly and Allergome Inference Re...mentioning
confidence: 99%
“…They found that miRNAs could bind to target allergen‐encoding mRNAs, thereby highlighting the role of miRNAs in regulating the expression of allergen‐encoding mRNAs in mites. These findings will help us develop novel treatment strategies for allergic diseases caused by dust mites 17 …”
mentioning
confidence: 95%